Productive Welfare, the East Asian 'Model' and Beyond: Placing Welfare Types in Greater China into Context. Issue 2 (2nd January 2014) - Hudson, John; Kühner, Stefan; Yang, Nan
<x content-type="archive" xml:space="preserve">Abstract</x> This article rounds off the themed section by reviewing broader debates within welfare state modelling relevant to Greater China. More specifically, it examines the now well-established literature around the East Asian 'model' of welfare, and related debates on the notion of a 'productive welfare' model. In so doing, it challenges simplistic classifications that present the region as representing a single model of welfare and, instead, highlights the diversity of welfare provision found within both Greater China and East Asia more generally. Building on the authors' earlier published work comparing East Asian welfare systems with those found across the OECD, it also challenges claims that the region is home to a distinct 'productive' model of welfare. The article ends by highlighting some key drivers that will shape future debates.